USING AUTHENTIC MATERIALS IN ENGLISH LANGUAGE TEACHING: BRIDGING THE GAP BETWEEN CLASSROOM AND REAL-LIFE CONTEXTS - Fayziev Alisher; Toshkuvvatov Khayrulla (Journals Park Publishing, 2024)
This article explores the significance of incorporating authentic materials in English language teaching to bridge the gap between the classroom and real-life contexts. Authentic materials, such as newspapers, magazines, advertisements, videos, and songs, reflect the language as used by native speakers in everyday life. By utilizing these resources, teachers can provide students with exposure to real-world language use, enhancing their listening, speaking, reading, and writing skills in a meaningful way. Additionally, authentic materials offer cultural insights and help students learn about the target language's culture. By selecting appropriate materials and scaffolding their use with activities, teachers can make language learning more relevant and practical for students, boosting their confidence and preparedness for real-life communication. Overall, the integration of authentic materials enriches students' language proficiency, cultural awareness, and overall learning experience by connecting the classroom with real-life contexts.
Keywords: authentic materials, English language teaching, classroom, real-life contexts, language proficiency, cultural awareness.